Interactive display (A) - Loh, Yong Tat (Nanyang Technological University, 2022)
A layman definition for interaction is action and reaction between people and things. The way of interaction has been evolving with technology as well. People used to interact with each other by talking, which gradually moved to writing, followed by a phone call to a video call now. Following the changes in how people interact, interaction between games have changed as well especially board games. Board games are traditionally played between two or more players, where players interact with each other and the game. With the implementation of Artificial Intelligence (AI) strategic games like Chess, Go, Shogi came to live. With proven track records AIs are capable of defeating world champions and experts with years of experience under their belts. Connect 4 is a two-player game where player take turns slotting chips into a 6x7 grid. Each player possesses chips in a specific color to differentiate their moves. The aim of the game is to align four chips of the same color in either horizontally, vertically, or diagonally. Amidst forming their own connection players must stop their opponents from making their connection as well. This project aims to recreate the game using electronic components such as addressable LEDs and arcade buttons. To increase interactivity of the game a Connect 4 playing AI was included to create a single player mode. To achieve this the AI must be able to detect moves made by player and run through its algorithm to determine the best move to counter the player or play toward its winning move.